2013
DOI: 10.1038/srep01043
|View full text |Cite
|
Sign up to set email alerts
|

Immune profiling with a Salmonella Typhi antigen microarray identifies new diagnostic biomarkers of human typhoid

Abstract: Current serological diagnostic assays for typhoid fever are based on detecting antibodies against Salmonella LPS or flagellum, resulting in a high false-positive rate. Here we used a protein microarray containing 2,724 Salmonella enterica serovar Typhi antigens (>63% of proteome) and identified antibodies against 16 IgG antigens and 77 IgM antigens that were differentially reactive among acute typhoid patients and healthy controls. The IgG target antigens produced a sensitivity of 97% and specificity of 80%, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 44 publications
2
96
0
Order By: Relevance
“…We therefore printed purified t1477 and four different sources of purified LPS in parallel lines on nitrocellulose membrane using a noncontact jet printer, and the membrane was dried and cut into immunostrips. Antigens t3710 and t1459 described in a previous study 10 were also printed, but were unreactive (not shown). Immunostrips were then probed with 56 randomized serum samples from the U.S. control, Nigerian healthy control, "No Growth," "Growth, S. Typhi," and "Growth, NTS" groups.…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…We therefore printed purified t1477 and four different sources of purified LPS in parallel lines on nitrocellulose membrane using a noncontact jet printer, and the membrane was dried and cut into immunostrips. Antigens t3710 and t1459 described in a previous study 10 were also printed, but were unreactive (not shown). Immunostrips were then probed with 56 randomized serum samples from the U.S. control, Nigerian healthy control, "No Growth," "Growth, S. Typhi," and "Growth, NTS" groups.…”
Section: Resultsmentioning
confidence: 68%
“…In previous studies, we described the production and use of a S. Typhi partial proteome microarray (∼63%) for profiling antibodies in human adult typhoid cases from Malawi, 9 Vietnam, 10 and Bangladesh, 18 and in the mouse S. Typhimurium model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations